2014
DOI: 10.1186/1742-2094-11-57
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microglia and infiltrating CD11c+ cells as antigen presenting cells for T cell proliferation and cytokine response

Abstract: BackgroundTissue-resident antigen-presenting cells (APC) exert a major influence on the local immune environment. Microglia are resident myeloid cells in the central nervous system (CNS), deriving from early post-embryonic precursors, distinct from adult hematopoietic lineages. Dendritic cells (DC) and macrophages infiltrate the CNS during experimental autoimmune encephalomyelitis (EAE). Microglia are not considered to be as effective APC as DC or macrophages.MethodsIn this work we compared the antigen present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 30 publications
6
117
0
Order By: Relevance
“…We also detected macrophages and microglia (Supplemental Fig. 1), both of which are able to act as antigen presenting cells, (26, 3133) as well as FoxP3 + /CD4 + T cells, which are likely to represent regulatory T cells (Supplemental Fig. 2).…”
Section: Resultsmentioning
confidence: 89%
“…We also detected macrophages and microglia (Supplemental Fig. 1), both of which are able to act as antigen presenting cells, (26, 3133) as well as FoxP3 + /CD4 + T cells, which are likely to represent regulatory T cells (Supplemental Fig. 2).…”
Section: Resultsmentioning
confidence: 89%
“…Thus, to compare MAMs and microglia between dural and parenchymal metastases, we analyzed the expression of MHCII and CD11c, markers that have been previously associated with the APC phenotype in microglia/macrophages [30, 31]. In line with studies from glioma and other non-cancerous CNS disorders [31, 32], flow cytometry analysis showed that only a small percentage of parenchymal microglia expressed MHCII or CD11c independent of the breast cancer model (range 3–30% and 2–6.5%, respectively; Figure 2D–2E, Supplementary Figure S4B, Supplementary Figure S5A–S5B). In the 4T1 and PyMT models, the proportion of MHCII-expressing MAMs was significantly higher in dural versus parenchymal metastases (84–92% versus 56–78%).…”
Section: Resultsmentioning
confidence: 99%
“…cytokine production). Several reports have suggested that CNS-infiltrating DCs may be crucial APCs for in situ restimulation of T cells (Bailey et al, 2007, Bartholomaus et al, 2009, Greter, Heppner, 2005, Odoardi et al, 2007, Pesic et al, 2013, Wlodarczyk et al, 2014). For example, several studies using in vivo imaging studies have shown that T cells encounter and form stable interactions with perivascular phagocytes prior to their infiltration of the CNS parenchyma (Bartholomaus, Kawakami, 2009, Odoardi, Kawakami, 2007, Pesic, Bartholomaus, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, several studies using in vivo imaging studies have shown that T cells encounter and form stable interactions with perivascular phagocytes prior to their infiltration of the CNS parenchyma (Bartholomaus, Kawakami, 2009, Odoardi, Kawakami, 2007, Pesic, Bartholomaus, 2013). Ex vivo T cell activation assays demonstrated that CD11b+ CD11c+ myeloid DCs are the most potent CNS APCs (Bailey, Schreiner, 2007), and a recent study demonstrated that while CD11c+ microglia express MHC II during EAE they do not license T cells to become Th1 and Th17 effectors cells (Wlodarczyk, Lobner, 2014). Subsequent studies have shown that CD11c+ cell MHCII expression is both sufficient (Greter, Heppner, 2005) and required (manuscript in preparation) for T cell restimulation in situ.…”
Section: Discussionmentioning
confidence: 99%